Hepatitis C hospitalizations in Spain, 2004-2013: a retrospective epidemiological study - R. Boix; R. Cano; P. Gallego; F. Vallejo; R. Fernández-Cuenca; I. Noguer; A. Larrauri (BMC, 2017)
Abstract Background Hepatitis C is an important public health problem about which there is currently scarce epidemiological information. The objective of this study is to describe and analyse the demographic and epidemiological characteristics of hospitalized cases of hepatitis C in the Spanish population between 2004 and 2013. Methods The study uses the Hospital Discharge Records Database of the Spanish National Health System. It is a retrospective descriptive epidemiological study. The variables analysed were year of infection, age, sex, diagnostic category, days admitted and co-morbidity. Results There have been a total of 351,996 hospitalizations; 225,138 men (64%) and 126,858 women (36%). They are divided between acute hepatitis 8161 (2.3%); chronic hepatitis 325,185 (92.4%) and unspecified hepatitis 18,650 (5.3%). The mean age for men is 53.7 (+/−15.2) and for women 62.3 (+/−17.3). 22.8% also present with an Human immunodeficiency virus (HIV) disease coinfection, and 14.7% with opioid dependencies. The trend is for a gradual increase in cases without statistical significance. Conclusions The Hepatitis C cases hospitalized had high levels of chronicity, which entails two distinct patterns of illness in men and women - who are affected in different age ranges.